Factors Associated with Self-esteem Levels in Generation Z Students at Universitas Muhammadiyah Jakarta: A Cross-sectional Study - Sitanggang, Tantri Wenny; Rivani, Beata; Susilawati (The Indonesian Institute of Science and Technology Research, 2025)
Generation Z faces significant mental health challenges, including low self-esteem. In Indonesia, over 30% of individuals experiencing low self-esteem do not receive adequate treatment. Among the approximately 2.5 million people with mental illnesses, around 40% report low self-esteem. This study aimed to identify factors associated with self-esteem levels among students at Universitas Muhammadiyah Jakarta in 2024. An analytical cross-sectional research design was employed, with probability sampling used to select 103 respondents. Data were collected through questionnaires and analyzed using the Chi-square test. Results indicated that the majority of Generation Z students with low self-esteem reported insufficient family support (67 students, 65.0%), limited peer support (69 students, 67.0%), and were predominantly female (67 students, 67.0%). Statistical analysis revealed significant associations between family support and self-esteem level (P = 0.001), peer support and self-esteem level (P = 0.030), and gender and self-esteem level (P = 0.005).